EP779 Survival and prognostic factors in women treated for ovarian cancer in western region of saudi arabia. (1st November 2019) - Anfinan, N; Sait, K; Alam, M; Noor Wali, AW; Haque, A; Sait, H
Abstract : Introduction/Background: Among gynecological malignancies, ovarian cancer is most common and is currently at number five position in most frequent causes of deaths related to the cancers. Methodology: Clinical data were collected retrospectively for women who underwent primary staging or debulking surgery. Progression free survival (PFS) was defined as the time interval from the date of primary surgery to the date of disease recurrence or death/last follow-up without recurrence. Overall survival (OS) was defined as the time interval from the date of the primary surgery to the date of death or last follow-up. Results: Total of 144 Epithelial Ovarian Cancer patients were analyzed for progression free survival (PFS) and overall survival (OS). The median PFS and OS were 33 and 43.5 months respectively. Increasing age was found significantly associated with median PFS (p≤0.002) and OS (p≤0.014). A significant association was observed between papillary serous and non serous histopathology in PFS (p≤0.003) as well as in OS (p≤0.044). Patients with non-serous histopathology had better PFS and OS than the patients having serous histopathology. Logistic regression analysis revealed a linear association between risk of disease progression and death with increasing age. Tumor stage III was significantly associated with the risk of disease progression (OR=8.27, 95% CI, 3.18–21.53, p≤0.001) as well risk of death (OR=0.07, 95% CI, 0.02–0.19, p≤0.001). Tumor grade 3 was also observed significantly associated with the progression of disease. Conclusion: There are number of reasonable factors known to be associated with long term survival such as clinical presentation of the disease status i.e., stage, grade, performance status, and burden of the disease. Disclosure: Nothing to disclose.